Total synthesis of Malabaricones A-D - 이예규 (The Graduate School, Ajou University, 2024)
The highly concise and efficient route to access naturally occurring diarylnonanoid malabaricones A–D has been developed starting from three commercially available building blocks in four steps. The key features of this approach is the Sonogashira cross-coupling to incorporate structurally diverse aryl groups and Pd/C-promoted concomitant hydrogenation and hydrogenolysis in a single operation to accomplish the total synthesis of the malabaricone family. This unified and divergent approach enables the preparation of novel structurally diverse malabaricone libraries
학위논문(석사)--약학과,2024. 2
Keywords: Pd/C; Sonogashira cross-coupling; diarylnonanoid; hydrogenation; hydrogenolysis; malabaricones A–D